1982
DOI: 10.1139/v82-402
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical reduction of quinoxalino[2,3-b]quinoxaline

Abstract: . Can. J. Chem. 60,2797Chem. 60, (1982. We have been interested for some time in the very low solubility in usual solvents (methanol, electrochemical reduction of heterocyclic com-acetonitrile, dimethylsulphoxide, dimethylformapounds with two 1,4-nitrogen atoms in a six-mem-mide). It can be dissolved in hot acetic acid or in bered ring. We now report the electrochemical cold trifluoroacetic acid. Our first attempts aimed reduction in protic and aprotic medium of the at obtaining an unambiguous determination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

1983
1983
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 3 publications
2
6
0
Order By: Relevance
“…Based on the electrochemical study of BRIM at BDDE, it was shown that the reduction occurred in one-step quasi-reversible mechanism, involving the transfer of two electrons and two protons. Accordingly, it was concluded that the reduction happened at the quinoxaline ring confirming the same mechanism as for other quinoxaline derivatives [10,11]. We have also reported electrochemical study and the method for determination of varenicline, the quinoxaline derivative, in tablets and in spiked plasma, at BDDE, glassy carbon (GCE) and hanging mercury electrode [10].…”
Section: Introductionsupporting
confidence: 60%
“…Based on the electrochemical study of BRIM at BDDE, it was shown that the reduction occurred in one-step quasi-reversible mechanism, involving the transfer of two electrons and two protons. Accordingly, it was concluded that the reduction happened at the quinoxaline ring confirming the same mechanism as for other quinoxaline derivatives [10,11]. We have also reported electrochemical study and the method for determination of varenicline, the quinoxaline derivative, in tablets and in spiked plasma, at BDDE, glassy carbon (GCE) and hanging mercury electrode [10].…”
Section: Introductionsupporting
confidence: 60%
“…31 The true structure of compound 6 was first determined in 1987 as benzenoid rather than quinonoid based on the AA¢XX¢ patterns for the protons of the terminal benzene rings in the corresponding 1 H NMR spectroscopic data. 32,33 Unfortunately, dihydrotetraazapentacene 6 has often been shown as the erroneous quinonoid structure in the literature until recently. [34][35][36] In connection with the debated structure of compound 6, our group found that the methylation of 6 yielded both benzenoid and quinonoid heteropentacenes 7 and 8 4b (Figure 4).…”
Section: A Dihydrotetraazapentacene and Its Methylated Derivativesmentioning
confidence: 99%
“…On cathodic sweep, one reversible wave was observed for all the compounds (see supplementary information) corresponding to the reduction of benzo[g]quinoxaline segment. 50 On cathodic sweep an irreversible wave was observed for compound 5 at −1.30 V which may be due to the reduction of -NO 2 group.…”
Section: Electrochemical Propertiesmentioning
confidence: 95%